Synthesis and Characterization of New Pyrano[2,3-c]pyrazole Derivatives as 3-Hydroxyflavone Analogues - Urbonavičius, Arminas; Krikštolaitytė, Sonata; Bieliauskas, Aurimas; Martynaitis, Vytas; Solovjova, Joana; Žukauskaitė, Asta; Arbačiauskienė, Eglė; Šačkus, Algirdas (Molecules (Basel, Switzerland), 2023)
In this paper, an efficient synthetic route from pyrazole-chalcones to novel 6-aryl-5-hydroxy-2-phenylpyrano[2,3-c]pyrazol-4(2H)-ones as 3-hydroxyflavone analogues is described. The methylation of 5-hydroxy-2,6-phenylpyrano[2,3-c]pyrazol-4(2H)-one with methyl iodide in the presence of a base yielded a compound containing a 5-methoxy group, while the analogous reaction of 5-hydroxy-2-phenyl-6-(pyridin-4-yl)pyrano[2,3-c]pyrazol-4(2H)-one led to the zwitterionic 6-(N-methylpyridinium)pyrano[2,3-c]pyrazol derivative. The treatment of 5-hydroxy-2,6-phenylpyrano[2,3-c]pyrazol-4(2H)-one with triflic anhydride afforded a 5-trifloylsubstituted compound, which was further used in carbon-carbon bond forming Pd-catalyzed coupling reactions to yield 5-(hetero)aryl- and 5-carbo-functionalized pyrano[2,3-c]pyrazoles. The excited-state intramolecular proton transfer (ESIPT) reaction of 5-hydroxypyrano[2,3-c]pyrazoles from the 5-hydroxy moiety to the carbonyl group in polar protic, polar aprotic, and nonpolar solvents was observed, resulting in well-resolved two-band fluorescence. The structures of the novel heterocyclic compounds were confirmed by 1H-, 13C-, 15N-, and 19F-NMR spectroscopy, HRMS, and single-crystal X-ray diffraction data.
Keywords: pyrano[2,3-c]pyrazoles; 3-hydroxyflavone; ESIPT; pyrazoles; NMR investigation; Algar–Flynn–Oyamada reaction